High-strength and pollution-resistant porcelain insulator and preparation process thereof
Patent Information
- Application Number
- CN202611013170.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]在瓷复合绝缘子的制造中,芯棒与瓷体之间的界面结合质量是决定整体性能的核心因素之一,目前常用的界面填充方式为直接机械套接配合粘合液涂覆,普通环氧树脂注胶体系玻璃化转变温度较低,在高温大电流工况下易软化变形,导致界面滑移或出现缝隙,产生局部放电和击穿的风险
1、本发明中,双酚A型氰酸酯通过三聚反应与二氨基二苯砜和环氧树脂E-51生成高交联密度的三嗪环结构,三嗪环是一个高度对称的六元环,这种对称性使分子内部的偶极矩相互抵消,构成的交联网络十分紧密,能有效限制分子链段的活动,进一步抑制极性基团在外电场下的运动,从而降低介电损耗,并赋予材料抗电击穿性能;同时,三嗪环作为一种高度致密、刚性的三维交联体系,该结构极大限制了高分子链在受热时的自由运动,从而赋予材料极低的热膨胀系数,并且,在降低注胶液的膨胀系数的同时,环氧树脂E51与双酚A型氰酸酯反应还会生成含五元噁唑烷酮环的柔性化学结构,这种结构相比三嗪环结构具备更高的柔性,能够被固定在刚性的三嗪环网络中,其柔性链段在温度变化时能通过自身构象的调整来吸收和缓冲残余的热应力,防止环氧树脂芯棒和瓷体材料长时间暴露外界环境,避免经过长时热胀冷缩效应而导致的应力集中和界面开裂情况。
Smart Images

Figure CN123017652A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of power transmission and transformation system technology, specifically to a high-strength pollution-resistant porcelain insulator and its manufacturing process. Background Technology
[0002] Insulators are key components in power transmission and transformation systems, used to support and suspend conductors and provide electrical insulation. Their performance directly affects the safe and stable operation of the power grid. Based on the main insulation material, insulators are mainly divided into three categories: porcelain insulators, glass insulators, and composite insulators. Porcelain insulators possess excellent weather resistance, aging resistance, and mechanical strength, and are widely used in high-voltage and ultra-high-voltage transmission lines and substations. The porcelain material itself is chemically stable, exhibiting outstanding resistance to ultraviolet radiation, corona discharge, and tracking, with a service life of up to several decades. However, traditional porcelain insulators have a high dielectric constant differential structure, resulting in a relatively low dielectric constant in the porcelain body. Under strong electric fields, the surface potential distribution is uneven, easily forming localized high-field-strength regions near the flange, leading to the risk of surface flashover. To balance the excellent weather resistance of porcelain insulators with the lightweight and high-strength characteristics of composite materials, porcelain composite insulators have emerged. These insulators typically consist of an internal epoxy glass fiber core as the load-bearing structure, surrounded by an external porcelain sheath or porcelain skirts. The epoxy glass fiber core rod has extremely high axial tensile strength and good insulation properties, bearing all the mechanical load of the conductor; the outer ceramic body plays a role in resisting electric arc, aging and preventing dirt deposition.
[0003] In the manufacturing of porcelain composite insulators, the quality of the interface bonding between the core rod and the porcelain body is one of the core factors that determine the overall performance. Currently, the commonly used interface filling method is direct mechanical bonding combined with adhesive coating. Ordinary epoxy resin injection system has a low glass transition temperature and is prone to softening and deformation under high temperature and high current conditions, which can lead to interface slippage or gaps, resulting in the risk of partial discharge and breakdown.
[0004] Furthermore, porcelain insulators are exposed to the outdoor environment for a long time, and it is difficult to avoid surface contamination. More importantly, the micro-cracks on the coating of porcelain insulators caused by temperature stress or external scratches during service cannot be actively repaired. Water droplets and dirt easily accumulate at the cracks, becoming the starting point of partial discharge, causing the self-cleaning function of the coating to rapidly decline with the use time.
[0005] Therefore, the present invention provides a high-strength, pollution-resistant porcelain insulator and its manufacturing process to solve the problems existing in the prior art. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a high-strength, pollution-resistant porcelain insulator and its manufacturing process.
[0007] A high-strength, pollution-resistant porcelain insulator consists of a porcelain body material, an epoxy glass fiber core rod placed inside the porcelain body material, and an injection liquid poured between the epoxy glass fiber core rod and the porcelain body material to form a support column. Silicone rubber is injection molded on the support column through a high-temperature vulcanization process to form a silicone rubber shed. A layer of self-cleaning coating liquid is sprayed on the outside of the silicone rubber shed. The raw materials for the ceramic body include calcium titanate, iron oxide, niobium pentoxide, syenite, alumina and clay; The raw materials for the injection solution include bisphenol A cyanate, trimethylolpropane, dibutyltin dilaurate, diaminodiphenyl sulfone, 2-methylimidazolium, nonylphenol, DMF and epoxy resin E-51; The raw materials for the self-cleaning coating liquid include vanillin, DMF, diphenylmethane diisocyanate, 4-fluorophenyl isocyanate, dibutyltin dilaurate, epoxy resin E-51, 4,4'-diaminodiphenylmethane, 2-methylimidazole, dibutyltin dilaurate, and nanofillers.
[0008] A manufacturing process for a high-strength, pollution-resistant porcelain insulator includes the following steps: S1: Preparation of injection solution Bisphenol A cyanate was added to a reaction flask for prepolymerization, then cooled. Trimethylolpropane was added to the prepolymerized bisphenol A cyanate, followed by dibutyltin dilaurate. The mixture was stirred and reacted, then cooled to room temperature to obtain a curing aid. Weigh diaminodiphenyl sulfone, 2-methylimidazolium and nonylphenol, add the above materials to DMF to dissolve, then add epoxy resin E-51 and add curing aid, stir evenly to obtain injection solution; S2: Preparation of ceramic materials Calcium titanate, iron oxide, niobium pentoxide, syenite, alumina and clay are mixed to obtain a mixture, which is then ball-milled and sieved. A binder is added and stirred evenly to obtain a billet. The blank is molded in a mold, degassed, dried, heated and held at a certain temperature, and then cooled in a furnace to obtain the ceramic material. S3: Fabrication of support columns The surface of the epoxy glass fiber core rod is polished, then coaxially placed in the channel in the center of the ceramic material and fixed. Then, the injection liquid prepared in step S1 is poured in to fill the gap between the inner wall of the ceramic material and the epoxy glass fiber core rod. Vacuum is drawn to remove air bubbles, the temperature is raised to 100-110℃ and held for 2-2.5h, then raised to 140-150℃ and held for 2-2.5h, and finally raised to 180-190℃ and held for 4h. Finally, the temperature is slowly lowered to room temperature at a cooling rate of 1℃ / min to obtain the support column. S4: Preparation of self-cleaning coating liquid Vanillin and anhydrous DMF were added to a reaction flask, heated, and stirred until completely dissolved. Diphenylmethane diisocyanate and 4-fluorophenyl isocyanate were mixed and added dropwise to the reaction flask under nitrogen protection, followed by the addition of dibutyltin dilaurate. The mixture was heated to obtain a prepolymer solution. Epoxy resin E-51 was dissolved in the mixed solvent and stirred. 4,4'-diaminodiphenylmethane was then added, followed by the addition of 2-methylimidazole and dibutyltin dilaurate. The mixture was stirred to obtain a pre-reaction solution, which was stored at room temperature. The prepolymer solution was added dropwise to the pre-reaction solution, and nanofillers were added. The mixture was ultrasonically dispersed and then vacuum rotary evaporated to obtain a self-cleaning coating solution. S5: Preparation of high-strength, pollution-resistant porcelain insulators The support column is placed in a silicone rubber injection mold, and the silicone rubber material is injected and pressed into shape through a high-temperature vulcanization process to form a silicone rubber shed on the support column. A layer of self-cleaning coating liquid is sprayed on the outside of the silicone rubber shed at a spraying pressure of 0.2-0.3MPa and the coating thickness is controlled at 50-80μm. It is first surface-dried at room temperature (22-24℃) for 1-2 hours, then heated to 70-80℃ for 2-3 hours, and then heated to 130-140℃ for 2-3 hours. It is then naturally cooled to room temperature (22-24℃) to obtain a high-strength pollution-resistant porcelain insulator.
[0009] Further, step S1, preparing the dispensing solution, includes the following steps: Bisphenol A cyanate was added to a reaction flask and prepolymerized in an oil bath at 160-180℃ for 1-2 hours. Then the temperature was lowered to 80-90℃, and trimethylolpropane was added to the prepolymerized bisphenol A cyanate at a molar ratio of 1:3. Then 0.1-0.3% of dibutyltin dilaurate by mass of the system was added, and the mixture was stirred at 100-200 r / min. Nitrogen gas was introduced during stirring and maintained for 5-10 minutes. Then the mixture was placed at 100-110℃ for 30-40 minutes, and then the temperature was increased to 110-120℃ and the reaction was continued for 1-1.5 hours. Finally, the mixture was cooled to room temperature to obtain the curing aid. Weigh 4-8 parts by weight of diaminodiphenyl sulfone, 0.5-2 parts by weight of 2-methylimidazole and 0.5-0.8 parts by weight of nonylphenol, add the above materials to 30-50 parts by weight of DMF and dissolve them, then add 100-110 parts by weight of epoxy resin E-51 and add 12-18% by weight of curing aid of epoxy resin, stir evenly to obtain the injection solution.
[0010] Further, step S2, preparing the ceramic material, includes the following steps: Mix 5-6 parts by weight of calcium titanate, 3-5 parts by weight of iron oxide, 1-3 parts by weight of niobium pentoxide, 5-10 parts by weight of syenite, 20-25 parts by weight of alumina and 15-20 parts by weight of clay to obtain a mixture. Add water and milling beads to the mixture and mill in a milling jar for 2-3 hours. Then pass through a 60-mesh sieve and add 5-10% of binder and stir evenly to obtain a billet. The blank is molded in a mold, degassed, and then heated to 150-160℃ to dry. Then, the temperature is increased to 1000-1150℃ at a rate of 5℃ / min and held for 2-4 hours. Then, the temperature is increased to 1250-1350℃ at a rate of 3℃ / min and held for 2-4 hours. The blank is then cooled in the furnace to obtain the ceramic material.
[0011] Further, step S4, preparing the self-cleaning coating liquid, includes the following steps: Add 20-35 parts by weight of vanillin and 40-50 parts by weight of anhydrous DMF to a reaction flask, purge with nitrogen, heat to 50-60℃, and stir until completely dissolved; mix 15-20 parts by weight of diphenylmethane diisocyanate and 5-10 parts by weight of 4-fluorophenyl isocyanate and add dropwise to the reaction flask under nitrogen protection, with a dropwise addition time of 30-40 min; then add 0.1-0.3 parts by weight of dibutyltin dilaurate, heat to 70-80℃, react for 2-3 h, and cool to room temperature to obtain a prepolymer solution; Dissolve 90-100 parts by weight of epoxy resin E-51 in 100-110 parts by weight of mixed solvent, stir for 20-30 minutes until completely dissolved, then add 15-25 parts by weight of 4,4'-diaminodiphenylmethane, followed by 0.5-1 parts by weight of 2-methylimidazole and 0.2-0.4 parts by weight of dibutyltin dilaurate, stir for 15-20 minutes to obtain a pre-reaction solution, and store at room temperature; The above prepolymer solution is added dropwise to the above pre-reaction solution over a period of 20-30 minutes. Then, the mixture is stirred at 500-600 r / min for 10-15 minutes. Next, 10-15% of the total mass of the nanofiller is added, and the mixture is ultrasonically dispersed for 20-30 minutes. Finally, the mixture is vacuum rotary evaporated for 20-30 minutes to obtain a self-cleaning coating solution.
[0012] Furthermore, the nanofiller is obtained by mixing nano-SiO2 and nano-TiO2 at a mass ratio of 1:1 and completely immersing them in HTMS silane coupling agent for 4-5 hours for modification, followed by washing and drying.
[0013] Furthermore, the mass ratio of the mixture, the milling beads, and the water is (1-1.5):2:1.
[0014] Furthermore, the adhesive is a 10wt% aqueous solution of polyvinyl alcohol.
[0015] Furthermore, the mold has a pre-drilled hole in the middle for placing an epoxy fiberglass core rod, and sealing grooves at both ends.
[0016] Furthermore, the mixed solvent is obtained by mixing DMF and ethyl acetate in a mass ratio of 2:1.
[0017] The present invention has the following advantages: 1. In this invention, bisphenol A cyanate reacts with diaminodiphenyl sulfone and epoxy resin E-51 via a trimerization reaction to form a triazine ring structure with high crosslinking density. The triazine ring is a highly symmetrical six-membered ring. This symmetry causes the dipole moments within the molecule to cancel each other out, resulting in a very tight crosslinking network that effectively restricts the movement of molecular chain segments, further suppressing the movement of polar groups under an external electric field, thereby reducing dielectric loss and imparting electrical breakdown resistance to the material. Simultaneously, as a highly dense and rigid three-dimensional crosslinking system, the triazine ring structure greatly restricts the free movement of polymer chains when heated. The reaction between epoxy resin E51 and bisphenol A cyanate produces a flexible chemical structure containing a five-membered oxazolidinone ring. This structure is more flexible than the triazine ring structure and can be fixed in a rigid triazine ring network. Its flexible segments can absorb and buffer residual thermal stress by adjusting their own conformation when the temperature changes, preventing the epoxy resin core rod and ceramic material from being exposed to the external environment for a long time, and avoiding stress concentration and interface cracking caused by long-term thermal expansion and contraction.
[0018] 2. The ceramic material formulation of this invention incorporates calcium titanate, iron oxide, and niobium pentoxide. Performance enhancement is achieved by introducing these functional components into the traditional clay-feldspar-alumina electrical porcelain system. Alkali metal oxides in syenite form a liquid phase that promotes ion migration. Tetravalent titanium in calcium titanate embeds into the alumina lattice to form a solid solution and promotes in-situ formation of platy mullite. Simultaneously, it reacts with alumina to generate low-expansion aluminum titanate. Iron oxide further participates in solid solution and grain control. Niobium pentoxide reacts with calcium oxide contained in the clay and syenite in the system to generate calcium niobate, which is anchored at the grain boundaries, thus constructing a dense, fine-grained microstructure. This microstructure endows the ceramic material with high mechanical strength and stable compressive strength. Meanwhile, the unreacted portions of calcium titanate, niobium pentoxide, and syenite can form a second phase, CaNb₂O₆. This crystalline phase has a wider band gap, thus increasing its resistivity as a ceramic material. Therefore, incorporating calcium titanate, iron oxide, and niobium pentoxide into the clay-feldspar-alumina electrical porcelain system achieves the dual benefits of high physical strength and high resistivity. When used in porcelain insulators, it can effectively suppress leakage current, reduce the risk of surface flashover, and meet the engineering requirements for the comprehensive performance of insulation components in high-voltage power transmission and transformation equipment.
[0019] 3. This invention uses vanillin, 4-fluorophenyl isocyanate, and 4,4'-diaminodiphenylmethane to prepare a self-cleaning coating liquid. The three components form a cross-linked network through the bridging effect of isocyanate. The fluorinated segments of vanillin and 4-fluorophenyl isocyanate are incorporated into the main chain of the epoxy resin. The fluorinated segments reduce the surface energy and impart hydrophobic properties. The aldehyde group of vanillin forms a dynamic chemical bond with the amino group. The formed dynamic chemical bond can undergo a reversible reaction when heated to 150°C, achieving self-repair. After introducing 4,4'-diaminodiphenylmethane, vanillin can react with a specific amine, 4,4'-diaminodiphenylmethane, to form a dynamic imine bond. The dynamic imine bond can undergo an exchange reaction at a lower temperature. At the same time, the fluorine atom structure of 4-fluorophenyl isocyanate further reduces the activation energy of the exchange reaction, lowering the high temperature required for vanillin self-repair to about 60°C. Porcelain insulators in power systems are exposed to the outdoor environment for extended periods. Microcracks on their surfaces easily accumulate dirt, leading to flashover accidents. If microcracks develop on the surface of the self-cleaning coating, water droplets can easily adhere, significantly reducing its self-cleaning performance. Therefore, the self-cleaning coating of this invention, which repairs microcracks visually, can significantly improve the self-cleaning ability of porcelain insulators and extend their service life. Attached Figure Description
[0020] Figure 1 This is a process flow diagram for the preparation of the high-strength, pollution-resistant porcelain insulator of the present invention. Detailed Implementation
[0021] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of this invention.
[0022] Example 1: A manufacturing process for a high-strength, pollution-resistant porcelain insulator, such as Figure 1 As shown, it includes the following steps: S1: Preparation of injection solution Bisphenol A cyanate was added to a reaction flask and prepolymerized in an oil bath at 160°C for 1 hour. The temperature was then lowered to 80°C, and trimethylolpropane was added to the prepolymerized bisphenol A cyanate at a molar ratio of 1:3. Then, 0.1% of dibutyltin dilaurate was added to the total mass of the system, and the mixture was stirred at 100 r / min. Nitrogen gas was introduced during the stirring process and maintained for 5 minutes. The mixture was then placed at 100°C for 30 minutes, and the temperature was increased to 110°C. The reaction was continued for 1 hour, and then cooled to room temperature to obtain the curing aid. Weigh 8 parts by weight of diaminodiphenyl sulfone, 0.5 parts by weight of 2-methylimidazole and 0.8 parts by weight of nonylphenol, add the above materials to 30 parts by weight of DMF and dissolve them, then add 110 parts by weight of epoxy resin E-51 and add 12% by weight of curing aid of epoxy resin, stir evenly to obtain the injection solution.
[0023] S2: Preparation of ceramic materials 5.5 parts by mass of calcium titanate, 4 parts by mass of iron oxide, 2 parts by mass of niobium pentoxide, 8 parts by mass of syenite, 22 parts by mass of alumina and 17 parts by mass of clay were mixed to obtain a mixture. Water and milling beads were added to the mixture, and the mass ratio of the mixture, milling beads and water was 1.2:2:1. The mixture was milled in a ball mill jar for 2.5 hours, then passed through a 60-mesh sieve. 8% binder was added and stirred evenly to obtain a blank. The binder was a 10wt% polyvinyl alcohol aqueous solution. The blank is molded in a mold, degassed, and then heated to 155°C and dried. The mold has a channel in the middle for placing an epoxy glass fiber core rod and sealing grooves at both ends. The temperature is then raised to 1100°C at a rate of 5°C / min and held for 3 hours. The temperature is then raised to 1300°C at a rate of 3°C / min and held for 3 hours. The blank is then cooled in the furnace to obtain the ceramic material.
[0024] S3: Fabrication of support columns The surface of the epoxy glass fiber core rod is polished, then coaxially placed in the channel in the center of the ceramic material and fixed. Then, the injection liquid prepared in step S1 is poured in to fill the gap between the inner wall of the ceramic material and the epoxy glass fiber core rod. Vacuum is drawn to remove air bubbles, the temperature is raised to 100℃ and held for 2 hours, then raised to 140℃ and held for 2 hours, and finally raised to 180℃ and held for 4 hours. Finally, the temperature is slowly lowered to room temperature at a cooling rate of 1℃ / min to obtain the support column.
[0025] S4: Preparation of self-cleaning coating liquid Add 30 parts by mass of vanillin and 45 parts by mass of anhydrous DMF to a reaction flask, purge with nitrogen, heat to 55°C, and stir until completely dissolved; mix 18 parts by mass of diphenylmethane diisocyanate and 7 parts by mass of 4-fluorophenyl isocyanate and add dropwise to the reaction flask under nitrogen protection for 35 min, then add 0.2 parts by mass of dibutyltin dilaurate, heat to 75°C, react for 2.5 h, cool to room temperature, and obtain a prepolymer solution; 95 parts by weight of epoxy resin E-51 were dissolved in 105 parts by weight of mixed solvent and stirred for 25 min until completely dissolved. Then 20 parts by weight of 4,4'-diaminodiphenylmethane were added, followed by 0.8 parts by weight of 2-methylimidazole and 0.3 parts by weight of dibutyltin dilaurate. The mixture was stirred for 18 min to obtain a pre-reaction solution, which was stored at room temperature. The mixed solvent was a mixture of DMF and ethyl acetate in a mass ratio of 2:1. The above prepolymer solution was added dropwise to the above pre-reaction solution over a period of 25 min. Then, the mixture was stirred at 550 r / min for 12 min. Next, 12% of the total mass of nanofiller was added, and the mixture was ultrasonically dispersed for 25 min. Then, the mixture was vacuum rotary evaporated for 25 min to obtain a self-cleaning coating solution. The nanofiller was prepared by mixing nano-SiO2 and nano-TiO2 in a 1:1 mass ratio and completely immersing them in HTMS silane coupling agent for 4.5 h for modification, followed by washing and drying.
[0026] S5: Preparation of high-strength, pollution-resistant porcelain insulators The support column is placed in a silicone rubber injection mold, and the silicone rubber material is injected and pressed into shape through a high-temperature vulcanization process to form a silicone rubber umbrella skirt on the support column. A layer of self-cleaning coating liquid is sprayed on the outside of the silicone rubber umbrella skirt at a spraying pressure of 0.2 MPa and a coating thickness of 50 μm. The coating is first surface-dried at room temperature (22°C) for 1 hour, then heated to 70°C for 2 hours, and then heated to 130°C for 2 hours. The coating is then naturally cooled to room temperature (22°C) to obtain a high-strength, pollution-resistant porcelain insulator.
[0027] Example 2: A manufacturing process for a high-strength, pollution-resistant porcelain insulator, such as Figure 1 As shown, it includes the following steps: S1: Preparation of injection solution Bisphenol A cyanate was added to a reaction flask and prepolymerized in an oil bath at 180°C for 2 hours. The temperature was then lowered to 90°C, and trimethylolpropane was added to the prepolymerized bisphenol A cyanate at a molar ratio of 1:3. Then, 0.1-0.3% of dibutyltin dilaurate was added to the total mass of the system. The mixture was stirred at 100-200 r / min, and nitrogen gas was introduced during stirring for 5-10 minutes. The mixture was then placed at 100-110°C for 30-40 minutes, and the temperature was increased to 110-120°C. The reaction was continued for 1-1.5 hours, and then cooled to room temperature to obtain the curing aid. Weigh 4 parts by weight of diaminodiphenyl sulfone, 2 parts by weight of 2-methylimidazole and 0.5 parts by weight of nonylphenol, add the above materials to 50 parts by weight of DMF and dissolve them, then add 100 parts by weight of epoxy resin E-51 and add 18% by weight of curing aid of epoxy resin, stir evenly to obtain the injection solution.
[0028] S2: Preparation of ceramic materials 5 parts by mass of calcium titanate, 3 parts by mass of iron oxide, 1 part by mass of niobium pentoxide, 5 parts by mass of syenite, 20 parts by mass of alumina and 20 parts by mass of clay were mixed to obtain a mixture. Water and milling beads were added to the mixture. The mass ratio of the mixture, milling beads and water was 1:2:1. The mixture was milled in a ball mill jar for 2 hours. Then it was passed through a 60-mesh sieve. 5% binder was added and stirred evenly to obtain a blank. The binder was a 10wt% polyvinyl alcohol aqueous solution. The blank is molded in a mold, degassed, and then heated to 150°C and dried. The mold has a channel in the middle for placing an epoxy glass fiber core rod and sealing grooves at both ends. The temperature is then raised to 1000°C at a rate of 5°C / min and held for 2 hours. The temperature is then raised to 1250°C at a rate of 3°C / min and held for 2 hours. The blank is then cooled in the furnace to obtain the ceramic material.
[0029] S3: Fabrication of support columns The surface of the epoxy glass fiber core rod is polished, then coaxially placed in the channel in the center of the ceramic material and fixed. Then, the injection liquid prepared in step S1 is poured in to fill the gap between the inner wall of the ceramic material and the epoxy glass fiber core rod. Vacuum is drawn to remove air bubbles, the temperature is raised to 110℃ and held for 2.5h, then raised to 150℃ and held for 2.5h, and finally raised to 190℃ and held for 4h. Finally, the temperature is slowly lowered to room temperature at a cooling rate of 1℃ / min to obtain the support column.
[0030] S4: Preparation of self-cleaning coating liquid Add 20 parts by mass of vanillin and 40 parts by mass of anhydrous DMF to a reaction flask, purge with nitrogen, heat to 50°C, and stir until completely dissolved; mix 15 parts by mass of diphenylmethane diisocyanate and 5 parts by mass of 4-fluorophenyl isocyanate and add dropwise to the reaction flask under nitrogen protection for 30 min, then add 0.1 parts by mass of dibutyltin dilaurate, heat to 70°C, react for 2 h, and cool to room temperature to obtain a prepolymer solution; 90 parts by weight of epoxy resin E-51 were dissolved in 100 parts by weight of mixed solvent and stirred for 20 minutes until completely dissolved. Then 15 parts by weight of 4,4'-diaminodiphenylmethane were added, followed by 0.5 parts by weight of 2-methylimidazole and 0.2-0.4 parts by weight of dibutyltin dilaurate. The mixture was stirred for 15 minutes to obtain a pre-reaction solution, which was stored at room temperature. The mixed solvent was a mixture of DMF and ethyl acetate in a mass ratio of 2:1. The prepolymer solution was added dropwise to the pre-reaction solution over a period of 20 min, followed by stirring at 500 r / min for 10 min. Then, 10% of the total mass of the nanofiller was added, and the mixture was ultrasonically dispersed for 20 min. Finally, it was vacuum rotary evaporated for 20 min to obtain a self-cleaning coating solution. The nanofiller was prepared by mixing nano-SiO2 and nano-TiO2 in a 1:1 mass ratio and completely immersing them in HTMS silane coupling agent for 4 h for modification, followed by washing and drying.
[0031] S5: Preparation of high-strength, pollution-resistant porcelain insulators The support column is placed in a silicone rubber injection mold, and the silicone rubber material is injected and pressed into shape through a high-temperature vulcanization process to form a silicone rubber shed on the support column. A layer of self-cleaning coating liquid is sprayed on the outside of the silicone rubber shed at a spraying pressure of 0.3MPa and the coating thickness is controlled at 80μm. It is first surface dried at room temperature (24℃) for 2 hours, then heated to 80℃ for 3 hours, and then heated to 140℃ for 3 hours. It is then naturally cooled to room temperature (24℃) to obtain a high-strength pollution-resistant porcelain insulator.
[0032] Example 3: A manufacturing process for a high-strength, pollution-resistant porcelain insulator, such as Figure 1 As shown, it includes the following steps: S1: Preparation of injection solution Bisphenol A cyanate was added to a reaction flask and prepolymerized at 170°C in an oil bath for 1.5 h. The temperature was then lowered to 85°C, and trimethylolpropane was added to the prepolymerized bisphenol A cyanate at a molar ratio of 1:3. Then, 0.2% of dibutyltin dilaurate was added to the total mass of the system, and the mixture was stirred at 150 r / min. Nitrogen gas was introduced during the stirring process and maintained for 8 min. The mixture was then placed at 105°C for 35 min, and the temperature was increased to 115°C. The reaction was continued for 1.2 h, and then cooled to room temperature to obtain the curing aid. Weigh 6 parts by weight of diaminodiphenyl sulfone, 1 part by weight of 2-methylimidazole and 0.6 parts by weight of nonylphenol, add the above materials to 40 parts by weight of DMF and dissolve them, then add 105 parts by weight of epoxy resin E-51 and add 15% by weight of curing aid of epoxy resin, stir evenly to obtain the injection solution.
[0033] S2: Preparation of ceramic materials 6 parts by mass of calcium titanate, 5 parts by mass of iron oxide, 3 parts by mass of niobium pentoxide, 10 parts by mass of syenite, 25 parts by mass of alumina and 20 parts by mass of clay were mixed to obtain a mixture. Water and milling beads were added to the mixture, and the mass ratio of the mixture, milling beads and water was 1.5:2:1. The mixture was milled in a ball mill jar for 3 hours, then passed through a 60-mesh sieve. 10% binder was added and stirred evenly to obtain a blank. The binder was a 10wt% polyvinyl alcohol aqueous solution. The blank is molded in a mold, degassed, and then heated to 160°C and dried. The mold has a channel in the middle for placing an epoxy glass fiber core rod and sealing grooves at both ends. The temperature is then raised to 1150°C at a rate of 5°C / min and held for 4 hours. The temperature is then raised to 1350°C at a rate of 3°C / min and held for 4 hours. The blank is then cooled in the furnace to obtain the ceramic material.
[0034] S3: Fabrication of support columns The surface of the epoxy glass fiber core rod is polished, then coaxially placed in the channel in the center of the ceramic material and fixed. Then, the injection liquid prepared in step S1 is poured in to fill the gap between the inner wall of the ceramic material and the epoxy glass fiber core rod. Vacuum is drawn to remove air bubbles, the temperature is raised to 105℃ and held for 2 hours, then raised to 145℃ and held for 2.5 hours, and finally raised to 180℃ and held for 4 hours. Finally, the temperature is slowly lowered to room temperature at a cooling rate of 1℃ / min to obtain the support column.
[0035] S4: Preparation of self-cleaning coating liquid Add 35 parts by mass of vanillin and 50 parts by mass of anhydrous DMF to a reaction flask, purge with nitrogen, heat to 60°C, and stir until completely dissolved; mix 20 parts by mass of diphenylmethane diisocyanate and 10 parts by mass of 4-fluorophenyl isocyanate and add dropwise to the reaction flask under nitrogen protection for 40 min, then add 0.3 parts by mass of dibutyltin dilaurate, heat to 80°C, react for 3 h, and cool to room temperature to obtain a prepolymer solution; 100 parts by weight of epoxy resin E-51 were dissolved in 110 parts by weight of mixed solvent and stirred for 30 min until completely dissolved. Then 25 parts by weight of 4,4'-diaminodiphenylmethane were added, followed by 1 part by weight of 2-methylimidazole and 0.4 parts by weight of dibutyltin dilaurate. The mixture was stirred for 20 min to obtain a pre-reaction solution, which was stored at room temperature. The mixed solvent was a mixture of DMF and ethyl acetate in a mass ratio of 2:1. The prepolymer solution was added dropwise to the pre-reaction solution over a period of 30 min, followed by stirring at 600 r / min for 15 min. Then, 15% of the total mass of the nanofiller was added, and the mixture was ultrasonically dispersed for 30 min. Finally, it was vacuum rotary evaporated for 30 min to obtain a self-cleaning coating solution. The nanofiller was prepared by mixing nano-SiO2 and nano-TiO2 in a 1:1 mass ratio and completely immersing them in HTMS silane coupling agent for 5 h for modification, followed by washing and drying.
[0036] S5: Preparation of high-strength, pollution-resistant porcelain insulators The support column is placed in a silicone rubber injection mold, and the silicone rubber material is injected and pressed into shape through a high-temperature vulcanization process to form a silicone rubber shed on the support column. A layer of self-cleaning coating liquid is sprayed on the outside of the silicone rubber shed at a spraying pressure of 0.3 MPa and the coating thickness is controlled at 60 μm. It is first surface dried at room temperature (23℃) for 2 hours, then heated to 70℃ for 3 hours, and then heated to 130℃ for 3 hours. It is then naturally cooled to room temperature (24℃) to obtain a high-strength pollution-resistant porcelain insulator.
[0037] Comparative Example 1: Compared with Example 1, the difference of Comparative Example 1 is that bisphenol A cyanate is not added in step S1, but bisphenol A cyanate is replaced by diphenylmethane diisocyanate by the same mass. The other steps remain unchanged, and it is referred to as Comparative Example 1.
[0038] Comparative Example 2: Compared with Example 1, Comparative Example 2 differs in that diaminodiphenyl sulfone is not added in step S1, but dicyandiamide is used to replace diaminodiphenyl sulfone by mass. The other steps remain unchanged, and it is referred to as Comparative Example 2.
[0039] Comparative Example 3: Compared with Example 1, the difference of Comparative Example 3 is that no injection liquid is added in step S3. Instead, the epoxy glass fiber core rod is polished to a suitable size and an adhesive is applied to the inside of the ceramic material. The epoxy glass fiber core rod is then directly bonded to the ceramic material. The adhesive is commercially available Aremco 805 epoxy resin glue.
[0040] Comparative Example 4: Compared with Example 1, the difference of Comparative Example 4 is that calcium titanate is not added in step S2, but calcium titanate is replaced by aluminum oxide by mass, while the other steps remain unchanged. It is referred to as Comparative Example 4.
[0041] Comparative Example 5: Compared with Example 1, Comparative Example 5 differs in that iron oxide is not added in step S2, but is replaced by aluminum oxide of equal mass. The other steps remain unchanged, and it is referred to as Comparative Example 5.
[0042] Comparative Example 6: Compared with Example 1, Comparative Example 6 differs in that niobium pentoxide is not added in step S2, but is replaced by an equal mass of aluminum oxide. The remaining steps remain unchanged, and it is referred to as Comparative Example 6.
[0043] Comparative Example 7: Compared with Example 1, Comparative Example 7 differs in that 4-fluorophenyl isocyanate is not added in step S4, but vanillin is used to replace 4-fluorophenyl isocyanate by mass, while the other steps remain unchanged. It is referred to as Comparative Example 7.
[0044] Comparative Example 8: Compared with Example 1, Comparative Example 8 differs in that 4,4'-diaminodiphenylmethane is not added in step S4, but vanillin is used to replace 4,4'-diaminodiphenylmethane by mass. The remaining steps are unchanged, and it is referred to as Comparative Example 8.
[0045] Comparative Example 9: Compared with Example 1, the difference of Comparative Example 9 is that the self-cleaning coating prepared in this application is not used in step S5. Instead, an existing self-cleaning coating is used for coating and curing. The raw materials of the existing self-cleaning coating are: 60% vulcanized silicone rubber, 30% waterborne polyurethane and 10% pigment. It is formed by high temperature molding on the surface of the umbrella skirt. The remaining steps are unchanged. It is referred to as Comparative Example 9.
[0046] The dielectric loss and breakdown field strength of Examples 1-3 and Comparative Examples 1-3 were tested at a frequency of 1MHz, as shown in Table 1. The dielectric loss was tested using the method in GB / T31838.8-2024 "Dielectric and resistive properties of solid insulating materials - Part 8: Determination of dielectric properties (AC method) - Relative permittivity and dielectric loss factor (frequency 1MHz~300MHz)"; the breakdown field strength was tested using the method in GB / T1408.1-2016 "Electrical strength test methods for insulating materials - Part 1: Test at power frequency", and the breakdown field strength was measured at a power frequency of 48-62Hz.
[0047] Table 1
[0048] As can be seen from Table 1, the dielectric loss of the example group was lower than that of the comparative example, while the breakdown field strength was higher. The dielectric loss tangent was 0.0049-0.0055, and the breakdown field strength was higher than 28.8kV / mm. In comparative example 1, bisphenol A type cyanate was replaced with diphenylmethane diisocyanate, and the dielectric loss tangent increased to 0.0154. Bisphenol A type cyanate can form a triazine ring structure with diaminodiphenol and epoxy resin. It has the characteristics of weak polarity, high rigidity and aromatic heterocyclic, so it has good adhesion performance. However, because of its low polarity, its dielectric loss is also lower. After replacement, the power frequency breakdown field strength was reduced because the same cross-linking network could not be formed.
[0049] In Comparative Example 2, diaminodiphenyl sulfone was replaced with dicyandiamide, and the power frequency breakdown field strength decreased to 21.6 kV / mm. Diaminodiphenyl sulfone has weak polarity and does not leave unreacted groups, so it can also have lower dielectric loss and higher breakdown field strength.
[0050] In Comparative Example 3, direct bonding without adhesive filler resulted in a sharp drop in breakdown field strength to 18.0 kV / mm. The injection of adhesive filler filled the air gap between the ceramic body and the core rod, expelling the air at the interface between the ceramic body and the core rod, making it difficult for partial discharge to occur, thus preventing partial discharge and breakdown.
[0051] The support columns prepared in step S3 of Examples 1-3 and Comparative Examples 1-3 were subjected to push-out shear tests after high-temperature-low-temperature cycling. The support columns prepared in step S3 of Examples 1-3 and Comparative Examples 1-3 were placed at 70°C for 8 hours and then at 20°C for 8 hours, and the cycle was repeated 5 times. Then, a push-out test was performed using a universal testing machine, and the maximum shear failure load was recorded as shown in Table 2.
[0052] Table 2
[0053] As shown in Table 2, the maximum shear failure load of the example group after high-temperature-low-temperature cycling was 22 kN. This indicates that the copolymerization of bisphenol A cyanate and epoxy resin forms a triazine ring-oxazolidinone interpenetrating network. The polar groups in the curing system form strong chemical bonds with the coupling agent on the surface of the ceramic body and the surface of the epoxy glass fiber core rod. At the same time, the adhesive solution penetrates into the micropores of the rough inner wall of the ceramic body and the gaps between the glass fiber bundles under vacuum assistance. After curing, dense micro-anchoring points are formed, which restrict the free movement of the polymer chains when heated. This gives the material an extremely low coefficient of thermal expansion and absorbs and buffers residual thermal stress through its own conformation adjustment, preventing stress concentration and interface cracking caused by long-term thermal expansion and contraction of the epoxy resin core rod and ceramic material. Comparative Example 1 uses diphenylmethane diisocyanate instead of bisphenol A cyanate, and Comparative Example 2 uses dicyandiamide instead of diaminodiphenyl sulfone. Bisphenol A cyanate can form a flexible chemical structure containing a five-membered oxazolidinone ring with epoxy resin E-51, while diaminodiphenyl sulfone is used to assist in the formation of the triazine ring. Without the five-membered oxazolidinone ring, there is no flexible chain segment that can absorb thermal stress, and without the triazine ring, it is difficult to reduce the coefficient of thermal expansion of the material. Therefore, after high-temperature-low-temperature cycling, the maximum shear failure load of Comparative Examples 1-2 is about 14-16 kN, which is not as good as that of the Example Group. Comparative Example 3 uses adhesive instead of injection fluid. It can be seen that the present invention eliminates interfacial air by injecting highly fluid injection fluid, which can avoid air cavities to the greatest extent and thus enhance the bonding strength between the epoxy glass fiber core rod and the ceramic material. Conventional adhesive technology cannot completely eliminate interfacial air by injecting fluid as the present invention, which leads to interface cracking or debonding of the epoxy resin core rod and ceramic material of the ceramic insulator after long-term thermal expansion and contraction.
[0054] The dielectric constant, dielectric loss, and volume resistivity of Examples 1-3 and Comparative Examples 4-6 were tested. The dielectric constant and dielectric loss were tested using the method in GB / T31838.8-2024 "Dielectric and resistive properties of solid insulating materials - Part 8: Determination of dielectric properties (AC method) - Relative dielectric constant and dielectric loss factor (frequency 1MHz~300MHz)". The volume resistivity was tested using the method in GB / T31838.2-2019 "Dielectric and resistive properties of solid insulating materials - Part 2: Resistive properties (DC method) - Volume resistance and volume resistivity". A DC voltage of 500V was applied using a high resistance meter, and the volume resistance was read after 1 minute, as shown in Table 3.
[0055] Table 3
[0056] As can be seen from Table 3, Examples 1-3 have high dielectric constants and low dielectric losses, while also exhibiting a dielectric constant of 6.0 × 10⁻⁶. 13 The volume resistivity above Ω·cm demonstrates that the incorporation of calcium titanate, iron oxide, and niobium pentoxide significantly reduces ionic conductivity loss and interfacial polarization loss, thus imparting high insulation properties to the material. The volume resistivity of Comparative Examples 4-6 drops sharply because the unreacted portions of calcium titanate, niobium pentoxide, and syenite can form a CaNb₂O₆ second phase. This phase has a wider band gap, thereby increasing its resistivity as a ceramic material. The volume resistivity of Comparative Examples 4-6 decreases due to the absence of the CaNb₂O₆ second phase and its dense structure.
[0057] The static water contact angles of Examples 1-3 and Comparative Examples 7-9 were tested according to the method in GB / T30693-2014 "Measurement of the contact angle between plastic film and water". Using an optical contact angle measuring instrument, 5 μL of deionized water was dropped onto the coating surface of Examples 1-3 and Comparative Examples 7-9, and the static water contact angles were measured, as shown in Table 4.
[0058] Table 4
[0059] A 20 μm wide and 5 mm long scratch was made on the surfaces of Examples 1-3 and Comparative Examples 7-9 using a scalpel to simulate a microcrack. In one group, the water contact angle at the scratch was measured before repair, followed by placement in a 60°C oven for 2 hours, and then the water contact angle at the scratch was measured after repair. In the other group, the water contact angle at the scratch was measured before repair, followed by placement in a 150°C oven for 2 hours, and then the water contact angle at the scratch was measured after repair. The results are shown in Table 5.
[0060] Table 5
[0061] As can be seen from Tables 4 and 5, the initial static water contact angle of the Example Group was above 116.2°, while that of Comparative Examples 7-8 was only 114.8° and 113.4°, and that of Comparative Example 9 was only 102.0°. This shows that the coating of the present invention has good hydrophobic function. After scratching with a blade, the static water contact angle of the Examples and Comparative Examples was 71.8-73.6°. The scratching destroyed the surface micro-nano structure and the fluorine-containing layer. In the subsequent baking process at 60°C, the dynamic imine bond formed by the aldehyde group of vanillin and the amino group of 4,4'-diaminodiphenylmethane underwent reversible breakage and recombination, driving the diffusion and fusion of molecular chains at the crack interface. After healing, the scratches and grooves disappeared, and the fluorinated segments re-covered the surface. The contact angles of Examples 1-3 recovered to near their initial levels, exhibiting the same function at 150°C. Comparative Examples 7-8, lacking 4-fluorophenyl isocyanate and 4,4'-diaminodiphenylmethane, showed that even after 2 hours of repair at 60°C, the contact angle remained less than 90°, only recovering to 100-110° at 150°C. This demonstrates that vanillin can react with a specific amine compound, 4,4'-diaminodiphenylmethane, to form dynamic imine bonds. These dynamic imine bonds can undergo exchange reactions at lower temperatures. Furthermore, the fluorine atom structure of 4-fluorophenyl isocyanate further reduces the activation energy of the exchange reaction, lowering the high temperature required for vanillin self-repair to 60°C. Comparative Example 9, lacking both vanillin and dynamic imine bonds, and with a coating made of ordinary polyurethane, could not actively heal its scratches, relying solely on slight thermal expansion to fill a very small portion of the defects. The contact angle only recovered to approximately 74° at both 60°C and 150°C.
[0062] The physical strength of the insulators was evaluated by conducting compressive load tests on Examples 1-3 and Comparative Examples 4-6 in GB / T 8287.1-2008 "Insulators for indoor and outdoor posts of systems with nominal voltage above 1000V - Part 1: Tests on porcelain or glass insulators". The results are shown in Table 6.
[0063] Table 6
[0064] As can be seen from Table 6, the compressive failure load of the example group reached over 182 kN, while that of comparative examples 4-6 was only 130-150 kN. This is because the alkali metal oxides in the syenite form a liquid phase that promotes ion migration, the tetravalent titanium in the calcium titanate is embedded in the alumina lattice to form a solid solution and promotes the in-situ formation of plate-like mullite, and at the same time reacts with alumina to form low-expansion aluminum titanate. On this basis, iron oxide further participates in solid solution and grain control, while niobium pentoxide reacts with the clay and calcium oxide contained in the syenite in the system to form calcium niobate, which is pinned to the grain boundaries, thereby constructing a dense and fine-grained microstructure. This microstructure can endow the ceramic material with high mechanical strength and stable compressive strength. All three are indispensable. Therefore, the compressive failure load of the example group is much higher than that of the comparative example group.
[0065] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims. Parts not described in detail in this specification are prior art known to those skilled in the art.
Claims
1. A high-strength, pollution-resistant porcelain insulator, characterized in that, It consists of a ceramic body material, an epoxy glass fiber core rod placed inside the ceramic body material, and an injection liquid poured between the epoxy glass fiber core rod and the ceramic body material to form a support column. Silicone rubber is injection molded on the support column through a high-temperature vulcanization process to form a silicone rubber umbrella skirt. A layer of self-cleaning coating liquid is sprayed on the outside of the silicone rubber umbrella skirt to obtain the product. The raw materials for the ceramic body include calcium titanate, iron oxide, niobium pentoxide, syenite, alumina and clay; The raw materials for the injection solution include bisphenol A cyanate, trimethylolpropane, dibutyltin dilaurate, diaminodiphenyl sulfone, 2-methylimidazolium, nonylphenol, DMF and epoxy resin E-51; The raw materials for the self-cleaning coating liquid include vanillin, DMF, diphenylmethane diisocyanate, 4-fluorophenyl isocyanate, dibutyltin dilaurate, epoxy resin E-51, 4,4'-diaminodiphenylmethane, 2-methylimidazole, dibutyltin dilaurate, and nanofillers.
2. A manufacturing process for a high-strength, pollution-resistant porcelain insulator, characterized in that, Includes the following steps: S1: Preparation of injection solution Bisphenol A cyanate was added to a reaction flask for prepolymerization, then cooled. Trimethylolpropane was added to the prepolymerized bisphenol A cyanate, followed by dibutyltin dilaurate. The mixture was stirred and reacted, then cooled to room temperature to obtain a curing aid. Weigh diaminodiphenyl sulfone, 2-methylimidazolium and nonylphenol, add the above materials to DMF to dissolve, then add epoxy resin E-51 and add curing aid, stir evenly to obtain injection solution; S2: Preparation of ceramic materials Calcium titanate, iron oxide, niobium pentoxide, syenite, alumina and clay are mixed to obtain a mixture, which is then ball-milled and sieved. A binder is added and stirred evenly to obtain a billet. The blank is molded in a mold, degassed, dried, heated and held at a certain temperature, and then cooled in a furnace to obtain the ceramic material. S3: Fabrication of support columns The surface of the epoxy glass fiber core rod is polished, then coaxially placed in the channel in the center of the ceramic material and fixed. Then, the injection liquid prepared in step S1 is poured in to fill the gap between the inner wall of the ceramic material and the epoxy glass fiber core rod. Vacuum is drawn to remove air bubbles, the temperature is raised to 100-110℃ and held for 2-2.5h, then raised to 140-150℃ and held for 2-2.5h, and finally raised to 180-190℃ and held for 4h. Finally, the temperature is slowly lowered to room temperature at a cooling rate of 1℃ / min to obtain the support column. S4: Preparation of self-cleaning coating liquid Vanillin and anhydrous DMF were added to a reaction flask, heated, and stirred until completely dissolved. Diphenylmethane diisocyanate and 4-fluorophenyl isocyanate were mixed and added dropwise to the reaction flask under nitrogen protection, followed by the addition of dibutyltin dilaurate. The mixture was heated to obtain a prepolymer solution. Epoxy resin E-51 was dissolved in the mixed solvent and stirred. 4,4'-diaminodiphenylmethane was then added, followed by the addition of 2-methylimidazole and dibutyltin dilaurate. The mixture was stirred to obtain a pre-reaction solution, which was stored at room temperature. The prepolymer solution was added dropwise to the pre-reaction solution, and nanofillers were added. The mixture was ultrasonically dispersed and then vacuum rotary evaporated to obtain a self-cleaning coating solution. S5: Preparation of high-strength, pollution-resistant porcelain insulators The support column is placed in a silicone rubber injection mold, and the silicone rubber material is injected and pressed into shape through a high-temperature vulcanization process to form a silicone rubber shed on the support column. A layer of self-cleaning coating liquid is sprayed on the outside of the silicone rubber shed at a spraying pressure of 0.2-0.3MPa and the coating thickness is controlled at 50-80μm. It is first surface-dried at room temperature (22-24℃) for 1-2 hours, then heated to 70-80℃ for 2-3 hours, and then heated to 130-140℃ for 2-3 hours. It is then naturally cooled to room temperature (22-24℃) to obtain a high-strength pollution-resistant porcelain insulator.
3. The preparation process of the high-strength, pollution-resistant porcelain insulator according to claim 2, characterized in that, Step S1 involves preparing the dispensing solution, including the following steps: Bisphenol A cyanate was added to a reaction flask and prepolymerized in an oil bath at 160-180℃ for 1-2 hours. Then the temperature was lowered to 80-90℃, and trimethylolpropane was added to the prepolymerized bisphenol A cyanate at a molar ratio of 1:
3. Then 0.1-0.3% of dibutyltin dilaurate by mass of the system was added, and the mixture was stirred at 100-200 r / min. Nitrogen gas was introduced during stirring and maintained for 5-10 minutes. Then the mixture was placed at 100-110℃ for 30-40 minutes, and then the temperature was increased to 110-120℃ and the reaction was continued for 1-1.5 hours. Finally, the mixture was cooled to room temperature to obtain the curing aid. Weigh 4-8 parts by weight of diaminodiphenyl sulfone, 0.5-2 parts by weight of 2-methylimidazole and 0.5-0.8 parts by weight of nonylphenol, add the above materials to 30-50 parts by weight of DMF and dissolve them, then add 100-110 parts by weight of epoxy resin E-51 and add 12-18% by weight of curing aid of epoxy resin, stir evenly to obtain the injection solution.
4. The preparation process of the high-strength, pollution-resistant porcelain insulator according to claim 3, characterized in that, Step S2 involves preparing the ceramic material, including the following steps: Mix 5-6 parts by weight of calcium titanate, 3-5 parts by weight of iron oxide, 1-3 parts by weight of niobium pentoxide, 5-10 parts by weight of syenite, 20-25 parts by weight of alumina and 15-20 parts by weight of clay to obtain a mixture. Add water and milling beads to the mixture and mill in a milling jar for 2-3 hours. Then pass through a 60-mesh sieve and add 5-10% of binder and stir evenly to obtain a billet. The blank is molded in a mold, degassed, and then heated to 150-160℃ to dry. Then, the temperature is increased to 1000-1150℃ at a rate of 5℃ / min and held for 2-4 hours. Then, the temperature is increased to 1250-1350℃ at a rate of 3℃ / min and held for 2-4 hours. The blank is then cooled in the furnace to obtain the ceramic material.
5. The preparation process of the high-strength pollution-resistant porcelain insulator according to claim 4, characterized in that, Step S4 involves preparing the self-cleaning coating liquid, including the following steps: Add 20-35 parts by weight of vanillin and 40-50 parts by weight of anhydrous DMF to a reaction flask, purge with nitrogen, heat to 50-60℃, and stir until completely dissolved; mix 15-20 parts by weight of diphenylmethane diisocyanate and 5-10 parts by weight of 4-fluorophenyl isocyanate and add dropwise to the reaction flask under nitrogen protection, with a dropwise addition time of 30-40 min; then add 0.1-0.3 parts by weight of dibutyltin dilaurate, heat to 70-80℃, react for 2-3 h, and cool to room temperature to obtain a prepolymer solution; Dissolve 90-100 parts by weight of epoxy resin E-51 in 100-110 parts by weight of mixed solvent, stir for 20-30 minutes until completely dissolved, then add 15-25 parts by weight of 4,4'-diaminodiphenylmethane, followed by 0.5-1 parts by weight of 2-methylimidazole and 0.2-0.4 parts by weight of dibutyltin dilaurate, stir for 15-20 minutes to obtain a pre-reaction solution, and store at room temperature; The above prepolymer solution is added dropwise to the above pre-reaction solution over a period of 20-30 minutes. Then, the mixture is stirred at 500-600 r / min for 10-15 minutes. Next, 10-15% of the total mass of the nanofiller is added, and the mixture is ultrasonically dispersed for 20-30 minutes. Finally, the mixture is vacuum rotary evaporated for 20-30 minutes to obtain a self-cleaning coating solution.
6. The preparation process of the high-strength pollution-resistant porcelain insulator according to claim 1, characterized in that, The nanofiller was obtained by mixing nano-SiO2 and nano-TiO2 in a 1:1 mass ratio and completely immersing them in HTMS silane coupling agent for 4-5 hours for modification, followed by washing and drying.
7. The preparation process of the high-strength pollution-resistant porcelain insulator according to claim 4, characterized in that, The mass ratio of the mixture, milling beads, and water is (1-1.5):2:
1.
8. The preparation process of the high-strength pollution-resistant porcelain insulator according to claim 4, characterized in that, The adhesive is a 10wt% aqueous solution of polyvinyl alcohol.
9. The manufacturing process of the high-strength, pollution-resistant porcelain insulator according to claim 4, characterized in that, The mold has a pre-drilled hole in the middle for placing the epoxy fiberglass core rod, and sealing grooves at both ends.
10. The preparation process of the high-strength pollution-resistant porcelain insulator according to claim 5, characterized in that, The mixed solvent was obtained by mixing DMF and ethyl acetate in a mass ratio of 2:1.